Efficacy of daclizumab beta versus intramuscular interferon beta-1a on disability progression across patient demographic and disease activity subgroups in DECIDE. (December 2018) - Cohan, Stanley; Kappos, Ludwig; Giovannoni, Gavin; Wiendl, Heinz; Selmaj, Krzysztof; Havrdová, Eva Kubala; Rose, John; Greenberg, Steven; Phillips, Glenn; Ma, Wei; Wang, Ping; Lima, Gabriel; et al.
Background: Demonstration of clinical benefits on disability progression measures is an important attribute of effective multiple sclerosis (MS) treatments. Objective: Examine efficacy of daclizumab beta versus intramuscular (IM) interferon beta-1a on measures of disability progression in patient subgroups from DECIDE. Methods: Twenty-four-week confirmed disability progression (CDP), 24-week sustained worsening on a modified Multiple Sclerosis Functional Composite (MSFCS) where 3-Second Paced Auditory Serial Addition Test was replaced by Symbol Digit Modalities Test, and proportion of patients with clinically meaningful worsening in 29-Item Multiple Sclerosis Impact Scale physical impact subscale (MSIS-29 PHYS) score from baseline to week 96 were examined in the overall population and subgroups defined by baseline demographic/disease characteristics. Results: Daclizumab beta significantly reduced risk of 24-week CDP (hazard ratio (HR), 0.73; 95% confidence interval (95% CI), 0.55–0.98), risk of 24-week sustained MSFCS progression (HR, 0.80; 95% CI, 0.67–0.95), and odds of clinically meaningful worsening in MSIS-29 PHYS (odds ratio, 0.76; 95% CI, 0.60–0.95) versus IM interferon beta-1a. Point estimates showed trends favoring daclizumab beta over IM interferon beta-1a across several patient subgroups for all three outcome measures. Conclusion: Daclizumab beta showed consistent benefit versus IM interferon beta-1a across measures assessing patient disability/function and across a range of clinical baseline characteristics in patients with relapsing-remitting MS.